The impact of integration between audit committees and internal audit on improving the quality of financial performance in the health sector. (Case study of Khartoum State hospitals). - Hamid, Dr. Al-Tayeb (The Gulf Economist, 2026)
This research aims to explore the impact of integration between audit committees and internal auditing, as well as the characteristics and standards of internal audit, within the healthcare sector in Khartoum State. The researcher employed a deductive approach to define the research problem and formulate scientific hypotheses, and utilized statistical analysis methods in the field study, The research concludes that a robust internal audit system provides assurance and peace of mind to management and the organizational environment. Since the internal audit department focuses on both financial and administrative controls, it contributes to performance enhancement, expenditure rationalization, and protection of institutional assets. The study recommends the enactment of laws and regulations mandating both large and medium-sized healthcare institutions to establish audit committees